2009
DOI: 10.1111/j.1551-6709.2009.01059.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Routes to Face Perception: Evidence From Psychophysics and Computational Modeling

Abstract: The aim of this study was to separately analyze the role of featural and configural face representations. Stimuli containing only featural information were created by cutting the faces into their parts and scrambling them. Stimuli only containing configural information were created by blurring the faces. Employing an old-new recognition task, the aim of Experiments 1 and 2 was to investigate whether unfamiliar faces (Exp. 1) or familiar faces (Exp. 2) can be recognized if only featural or configural informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 58 publications
(113 reference statements)
3
29
1
Order By: Relevance
“…However, her study differed from ours in that she presented emotional expressions only for 100 ms, while we presented them until the participants responded. Thus, in Prkachin's study the short presentation time could have biased participants towards a configural mode of processing, as detailed analysis of features requires more time (Schwaninger et al, 2009). This could explain the different sensitivity to inversion in the two studies.…”
Section: Discussionmentioning
confidence: 97%
“…However, her study differed from ours in that she presented emotional expressions only for 100 ms, while we presented them until the participants responded. Thus, in Prkachin's study the short presentation time could have biased participants towards a configural mode of processing, as detailed analysis of features requires more time (Schwaninger et al, 2009). This could explain the different sensitivity to inversion in the two studies.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies suggest that both featural (piecemeal) and configural (holistic) processing make important contributions to face recognition [Sergent 1984;Cabeza and Kato 2000;Collishaw and Hole 2000;Ingvalson and Wenger 2005;Rhodes et al 2006;Schwaninger et al 2009;. Moreover, these two processes are dissociable [Cabeza and Kato 2000;Schwaninger et al 2009;, suggesting a dual-model hypothesis [Ingvalson and Wenger 2005;Schwaninger et al 2009;.…”
Section: Multimedia Processingmentioning
confidence: 94%
“…Moreover, these two processes are dissociable [Cabeza and Kato 2000;Schwaninger et al 2009;, suggesting a dual-model hypothesis [Ingvalson and Wenger 2005;Schwaninger et al 2009;. Research has also shown that recognition of novel faces, compared to learned faces, relies relatively more on the processing of 7:4 • S. Fan et al featural information.…”
Section: Multimedia Processingmentioning
confidence: 94%
“…For example, Schwaninger and colleagues (Schwaninger, Lobmaier, Wallraven, & Collishaw, 2009) compared faces with faces that had their features spatially scrambled. They found that the part-scrambled versions were not more difficult to recognise than the faces in which features were placed in their correct categorical relational position but with distorted metrical distances, which indicates a featural route to face recognition.…”
Section: Discussionmentioning
confidence: 99%